Air flow measurement and sensor calibration in air duct - Low, Emily Ying Ting (2016)
This report presents a measurement study on the airflow measurement technique with Pitot Tube customised by NTU in comparison with the commercially available Pitot Tubes. The major testing was done based on the testing bed simulated in the laboratory. An airflow testing bed that consists of a vortex flow meter pressure difference sensor, a centrifugal fan, air ducts, a damper and a calibrator was the chosen simulation set up in which the measurements was taken. Each damper angle was measured and adjusted accordingly at intervals during the measurement controlling the effects of pressure difference flowing into the pressure sensor. Air flow rate was controlled by adjusting the voltages of supplied to the centrifugal fan, where the air generated will then flow through the air ducts and into an air pressure sensor (Pitot Tube) where the differential pressures were measured. The collected measurements were later used In calculations to determine the accuracy of the measuring sensor device (Pitot Tube). The accuracy of the sensor was determined after rounds of calculations determining and considering the variance and changes in pressure as well as the variance in angles of the damper blades was taken into consideration when the test was performed. Future work would be required to further reaffirm the efficiency and effectiveness as well as the possibility of implementing the current design of the sensor commercially.